2011
DOI: 10.1007/s00425-011-1563-0
|View full text |Cite
|
Sign up to set email alerts
|

GsZFP1, a new Cys2/His2-type zinc-finger protein, is a positive regulator of plant tolerance to cold and drought stress

Abstract: Plant acclimation to environmental stress is controlled by a complex network of regulatory genes that compose distinct stress-response regulons. The C2H2-type zinc-finger proteins (ZFPs) have been implicated in different cellular processes involved in plant development and stress responses. Through microarray analysis, an alkaline (NaHCO(3))-responsive ZFP gene GsZFP1 was identified and subsequently cloned from Glyycine soja. GsZFP1 encodes a 35.14 kDa protein with one C2H2-type zinc-finger motif. The QALGGH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…And apart from involvement in oxidation and revival reactions and enzyme activating, Zn also plays main roles in regulation of protein synthesis and carbohydrates metabolism (Mousavi 2011). It's worth noting that the up-expression of zinc finger protein can increase Pro and SS accumulations in Arabidopsis and rice under water deficit (Xu et al 2008;Luo et al 2012). These previous evidences are conducive to explain our observations that SP and SS contents were all enhanced by supplemental Zn in cotton under PEG-6000 simulated drought stress (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…And apart from involvement in oxidation and revival reactions and enzyme activating, Zn also plays main roles in regulation of protein synthesis and carbohydrates metabolism (Mousavi 2011). It's worth noting that the up-expression of zinc finger protein can increase Pro and SS accumulations in Arabidopsis and rice under water deficit (Xu et al 2008;Luo et al 2012). These previous evidences are conducive to explain our observations that SP and SS contents were all enhanced by supplemental Zn in cotton under PEG-6000 simulated drought stress (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Besides, findings have shown that Zn is closely related to oxidative stress-induced expression of genes encoding APX (Tsonev and Lidon 2012). It's worth noting that the cotton Cys2/His2-type zinc-finger protein is associated with the response to drought stress in plant (Li et al 2010;Luo et al 2012), and overexpression of zinc-finger proteins are related to antioxidative defense by enhancing antioxidant enzymes activities and decreasing accumulation of MDA in rice (Zhang et al , 2014. Therefore, the SOD, CAT and APX activities were enhanced by supplemental Zn in cotton leaves (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…For example, transgenic Arabidopsis plants expressing GsZFP1 are more tolerant to cold and drought stresses (Luo et al 2012). Strong induction of OsMSR15 expression by heat, cold and drought stresses suggests that this gene might be involved in stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been already reported that WD-40 protein is expressed under salt stress in various plants such as BnSWD1 fromin Brassica napus 38, SRWD in Oryza sativa 39, SiWD40 in foxtail millet40 and WD40 repeat protein in Medicago trunculata 41. Other TFs like C2H2 have been reported to play important role in biological processes and various abiotic stresses, involving cold, drought, oxidative and salt stress in rice4243; cold and drought stress in soybean44 and osmotic, cold and mechanical stress in poplar45. This suggests that C2H2-ZFPs are likely to be associated with multiple physiological processes and stress responses in this salt tolerant land race of wheat also46.…”
Section: Discussionmentioning
confidence: 99%